The Provision for Agricultural Credit in the United States - Black, A. G. (Quarterly Journal of Economics, 1928)
Provisions for Agricultural Credit prior to 1913. — I. Federal rural-credit legislation since 1913, 95. — State rural-credit legislation since 1913, 103. — II. Effect of the new institutions. — Mortgage credit, 108. — Short-term credit, 111. — Terms of loans and interest rates, 115. — III. Adequacy of mortgage credit facilities, 117. — Provisions for "low-grade" loans, 120. — Appraisal methods, 122. — Mortgage credit facilities in the South, 123. — IV. Short-term credit facilities are inadequate, 124. — Bank failures, 124. — Suggestions for improvement of the country banking situation, 127. — V. Intermediate credit. Production credit in the South, 129. — VI. Conclusion, 130.